2010
DOI: 10.1186/1746-1596-5-68
|View full text |Cite
|
Sign up to set email alerts
|

Death-related gastric necrosis after Laparoscopic Adjustable Gastric Banding in the early post-operative period

Abstract: We report a case of a rare complication of Laparoscopic Adjustable Gastric Banding (LAGB) as a cause of death in the immediate post-operative period. The number of relevant reports and postmortem images presented in the literature is extremely restricted. Gastric necrosis may constitute a cause of death after LAGB in the early post-operative period. Postmortem examination reveals the extension of gastric ischemia and necrosis, responsible for the lethal outcome. To date, only one case of gastric necrosis after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…All papers relevant to this study were reviewed and of these, 22 papers have been included in this study. The findings of the cases with gastric necrosis following LAGB including details of : a) reference #, b) author, c) study type, d) number of cases/patients reported, e) age and sex, f) time interval between LAGB and gastric necrosis, g) presenting symptoms, h) management, i) outcome and j) cause of the gastric necrosis are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Review and Discussionmentioning
confidence: 99%
“…All papers relevant to this study were reviewed and of these, 22 papers have been included in this study. The findings of the cases with gastric necrosis following LAGB including details of : a) reference #, b) author, c) study type, d) number of cases/patients reported, e) age and sex, f) time interval between LAGB and gastric necrosis, g) presenting symptoms, h) management, i) outcome and j) cause of the gastric necrosis are summarized in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Adjustable gastric banding can cause death via pressure necrosis of the stomach wall. 5 Liver cirrhosis-which can be caused by obesity as such-is associated with increased mortality resulting from major surgery, 6 and might be expected to contribute to death from BS. However, apart from one case in the NCEPOD series, this is not generally reported.…”
Section: Direct Surgery-related Deaths and Deaths From Indi-mentioning
confidence: 99%
“…On literature review, only two cases of mortality in the early post-operative period were due to stomach necrosis as a complication of LAGB(5). …”
Section: Introductionmentioning
confidence: 99%